Odpowiedzi

2010-03-29T18:00:45+02:00
A) k=7n ;n
7n = k /: 7
n = k/7

b) a=k+6 ;k
k + 6 = a
k = a - 6

c) z=7-y ;y
7 - y = z
-y = z - 7 /: (-1)
y = -z + 7

d) d=a+bc ;c
a + bc = d
bc = d - a /: b
c = (d - a) : b

e) x=2k+1 ;k
2k + 1 = x
2k = x - 1 /: 2
k = (x - 1) : 2

f) 2k=7n+5 ;n
7n + 5 = 2k
7n = 2k - 5 /: 7
n = (2k - 5) : 7
2010-03-29T18:01:02+02:00
A)k=7n
n=k/7

b)a=k+6
k=a-6

c)z=7-y
-y=z-7
y=-z+7

d)d=a+bc
bc=d-a
c=(d-a)/b

e)x=2k+1
2k=x-1
k=(x-1)/2

f)2k=7n+5 powiedzmy że chodzi tu o n
7n=2k-5
n=(2k-5)/7